Transisi Strategi Mempertahankan Kopi Starling Pasca Teguran Satpol PP - Zahra Aulia Hariyanto; Puput Sri Wahyu Wulandari; Rauly Sijabat (INDO PUBLISHING, 2026)
This study aims to analyze the strategy transition undertaken by Starling Coffee vendors to sustain their businesses following reprimands or enforcement actions by the Municipal Police (Satpol PP). Using a qualitative approach with in-depth interviews and observations involving vendors and Satpol PP officers in Semarang City, the research is examined through the lens of Pierre Bourdieu’s theory of Field, Capital, and Habitus. The findings reveal that vendors develop practical adaptation mechanisms, such as selecting “safe” locations based on real-time information and social networks, as well as cooperative communication with authorities. A vigilance habitus formed from enforcement experiences drives agile strategies to mitigate conflict risks and maintain customer loyalty. In conclusion, the sustainability of Starling Coffee businesses is supported by holistic adaptation capabilities that integrate social, cultural, and symbolic aspects in responding to regulatory pressures and market competition.